2020
DOI: 10.1103/physrevd.101.033007
|View full text |Cite
|
Sign up to set email alerts
|

Angular analysis of B¯D2*(D

Abstract: We derive the four-fold angular distribution for the semileptonic decayB → D * 2 (→ Dπ) ν where D * 2 (2460) is a tensor meson. We start with the most general beyond the Standard Model (SM) dimension-six effective Hamiltonian which comprises (axial)vector, (pseudo)scalar and tensor operators for both quark and lepton currents, and it also includes the right-handed neutrinos. The decay can be described by 16 transversity amplitudes and it provides a multitude of observables which can be extracted from data. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Owing to the approximate flavor symmetry, the form factors of the decays are very close to their strange counterparts. A comparison of the form factors at from this study with those of other groups is shown in Tables 5−8, where the original values from LFQM [9,10], ISGW2 [7], and LCSRB [17] are converted to meet the current definitions of form factors using the formulae in Appendix B. We can see that large differences exist among the form factors given by different groups.…”
Section: Numerical Results and Discussion Of The Form Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…Owing to the approximate flavor symmetry, the form factors of the decays are very close to their strange counterparts. A comparison of the form factors at from this study with those of other groups is shown in Tables 5−8, where the original values from LFQM [9,10], ISGW2 [7], and LCSRB [17] are converted to meet the current definitions of form factors using the formulae in Appendix B. We can see that large differences exist among the form factors given by different groups.…”
Section: Numerical Results and Discussion Of The Form Factorsmentioning
confidence: 93%
“…In this appendix, we give the relevant formulae used to convert the form factors defined in Refs. [7,9,10,17] to meet the current definitions, which can be obtained directly by comparing the corresponding hadronic matrix elements.…”
Section: Decaysmentioning
confidence: 99%
See 1 more Smart Citation